Predicting the Marital Instability based on Marital Justice and Coping Styles with the Mediating Role of Work-Family Conflict in Conflicting Couples - Bijani, Javad; Hashemi, Nezam; Seadatee shamir, Aboutaleb (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to predict marital instability based on marital justice and coping styles with the mediating role of work-family conflict in conflicting couples of the Law Enforcement Force. Methods: The research method was descriptive-correlational, and its statistical population consisted of couples who visited law enforcement force counseling centers in Tehran in 2019, and 300  individuals were selected as a statistical sample using the convenience sampling method (voluntary) and they responded to the marital instability scale by Edwards et al. (1987), the Marital Justice Scale by Ghaffari et al. (2013), the Ways of Coping questionnaire by Lazarus and Folkman (1985), and the Work-Family Conflict Questionnaire by Lezent Mirez, Berleg, and Mucmarian (1996). Pearson correlation coefficient and path analysis were used in SPSS to analyze data. Results: The results of path analysis indicated that coping styles and marital justice directly predicted marital instability in conflicting couples, and work-family conflict played a significant mediating role in the relationship between problem-oriented coping style and marital instability and the relationship between emotion-oriented coping style and marital instability (P=0.01). Furthermore, the work-family conflict played a significant mediating role in the relationship between marital justice and instability (P=0.01). Conclusion: Given the roles of coping styles, marital justice, and work-family conflict in predicting marital instability, it can be concluded that teaching effective coping styles, paying attention to role conflict (work-family conflict), and teaching the division of responsibilities between couples can prevent injuries that threaten the marital stability.